PENGARUH JARAK TANAM DAN PEMBERIAN KOMPOS TKKS TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) DI ANTARA SAWIT DI LAHAN GAMBUT - Nora, Elvi '; ', Murniati '; ', Idwar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Onion have high economic value that is suitable to be cultivated in peatlands. Efforts to increase onion production can be done with the use of peatlands that have been planted with oil palm immature. Peatlands are managed by the plant spacing and the addition of compost TKKS. The research objective was to determine the effect of plant spacing and composting TKKS the growth and production of onion in the oil palm plantations on peatlands. The research was done in experimentation area Faculty of Agroteknologi Universitas Riau, Rimbo Panjang village, Kampar from June to August 2015. The research was using the Randomized Block Design Factorial with two factors. The first factor of plant spacing with three levels namely: 10 cm x 10 cm, 20 cm x 10 cm dan 20 cm x 20 cm. The second factor of compost dose TKKS with four levels namely: 5, 10, 15 dan 20 ton/ha. Parameter observed wereplant height, relative growth rate, dry weight, fresh weight tuber per plot, total tuber, rim tuber and dry weighttuber per plot. The results showed that the combination of plant spacing and composting TKKS showed not significant on the growth and production of onion among the palm trees on peatlands Keyword: Onion, plant spacing, compost TKKS, peatla